PENINGKATAN DAYA SAING PRODUK-PRODUK DAERAH MELALUI PENGGUNAAN CO-BRANDING - Fitriyani Rahman; Nita Ariyani (Kajian Hukum, 2018)
Regional contributions through the use of co-branding are one of the solutions in advancing economic growth and increasing the competitiveness of regional superior products. Co-branding is a marketing strategy that is used together on one product or service. Broadly speaking, the common goal of branding is to increase the value of brand equity by increasing the strength of product brands in the regions to collaborate. Daerah Istimewa Yogyakarta (DIY) is the province that has 100% Jogya, Yogyakarta, and Yogyakarta traditions and has used co-branding in order to improve the competitiveness of its regional products.This research aims to find out, understand, study, and analyze the use of co-branding in order to improve the competitiveness of regional superior products. This research also tries to study, discuss, study and analyze ideal arrangement about the use of co-branding on regional superior products. This research was conducted using the type of normative juridical research, namely research focused on studying the application of rules or norms in positive law. The research approach used is the statutory approach, the conceptual approach, and the case approach. This research emphasizes the importance of using co-branding on regional superior products in order to increase the competitiveness of regional products and economic growth in each region that is stable and sustainable. Keywords : regional superior products, brand, co branding